Is reduction formula the only way?

Calculus Level 5

If the integral I = 0 π 1 cos 74 x 1 cos x d x \displaystyle{I=\int _{ 0 }^{ \pi }{ \frac { 1-\cos { 74x } }{ 1-\cos { x } } } \ dx} can be adjusted in the form of a π b 6 \frac { a{ \pi }^{ b } }{ 6 } , find the value of a + b a+b .


The answer is 445.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Vighnesh Raut
Apr 21, 2015

Let I m = 0 π 1 cos m x 1 c o s x d x { I }_{ m }=\int _{ 0 }^{ \pi }{ \frac { 1-\cos { mx } }{ 1-cosx } dx }

Now, for m=1,2,3 , I m { I }_{ m } = π , 2 π , 3 π \pi ,2\pi ,3\pi . So, claim : I m { I }_{ m } = m π m\pi

Proof by induction:

As I 1 { I }_{ 1 } is true , let the result be true for all positive integers k \le k where k N k\in N

Then, I k = 0 π 1 cos k x 1 c o s x d x = k π , f o r k = 1 , 2 , . . . , k 1 , k { I }_{ k }=\int _{ 0 }^{ \pi }{ \frac { 1-\cos { kx } }{ 1-cosx } dx } =k\pi ,\quad for\quad k=1,2,...,k-1,k\quad I k + 1 I k = 0 π ( 1 cos ( k + 1 ) x ) ( 1 c o s k x ) 1 c o s x d x { I }_{ k+1 }-{ I }_{ k }=\int _{ 0 }^{ \pi }{ \frac { (1-\cos { (k+1)x } )-(1-coskx) }{ 1-cosx } dx } = 0 π c o s k x c o s ( k + 1 ) x 1 c o s x d x =\int _{ 0 }^{ \pi }{ \frac { coskx-cos(k+1)x }{ 1-cosx } dx } = 0 π 2 s i n ( k + 1 2 ) x . s i n ( x 2 ) 2 s i n 2 ( x 2 ) d x =\int _{ 0 }^{ \pi }{ \frac { 2sin\left( k+\frac { 1 }{ 2 } \right) x.sin\left( \frac { x }{ 2 } \right) }{ 2{ sin }^{ 2 }\left( \frac { x }{ 2 } \right) } dx } = 0 π s i n ( k + 1 2 ) x s i n ( x 2 ) d x =\int _{ 0 }^{ \pi }{ \frac { sin\left( k+\frac { 1 }{ 2 } \right) x }{ { sin }\left( \frac { x }{ 2 } \right) } dx } Now substituting k = k-1 I k I k 1 = 0 π s i n ( k 1 2 ) x s i n ( x 2 ) d x { I }_{ k }-{ I }_{ k-1 }=\int _{ 0 }^{ \pi }{ \frac { sin\left( k-\frac { 1 }{ 2 } \right) x }{ sin\left( \frac { x }{ 2 } \right) } dx } ( I k + 1 I k ) ( I k I k 1 ) = 0 π s i n ( k + 1 2 ) x s i n ( k 1 2 ) x s i n x 2 d x \therefore ({ I }_{ k+1 }-{ I }_{ k })-({ I }_{ k }-{ I }_{ k-1 })=\int _{ 0 }^{ \pi }{ \frac { sin\left( k+\frac { 1 }{ 2 } \right) x-sin\left( k-\frac { 1 }{ 2 } \right) x }{ sin\frac { x }{ 2 } } dx } = 0 π 2 c o s k x s i n x 2 s i n x 2 d x =\int _{ 0 }^{ \pi }{ \frac { 2coskx\quad sin\frac { x }{ 2 } }{ sin\frac { x }{ 2 } } dx } = 2 [ s i n k x k ] 0 π = 0 ={ 2\left[ \frac { sinkx }{ k } \right] }_{ 0 }^{ \pi }=0 So, I k + 1 = 2 I k I k 1 { I }_{ k+1 }=2{ I }_{ k }-{ I }_{ k-1 }

I k + 1 = 2 k π ( k 1 ) π { I }_{ k+1 }=2k\pi -(k-1)\pi

Hence, I k + 1 = ( k + 1 ) π { I }_{ k+1 }=(k+1)\pi So, by induction I m = m π m N { I }_{ m }=m\pi \quad \forall \quad m\in N

I 74 = 74 π = 444 6 π 1 { I }_{ 74 }=74\pi =\frac { 444 }{ 6 } { \pi }^{ 1 } a+b=445

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...